Numerical analysis of elevated jet in crossflow - Bayraktar, Seyfettin; Yilmaz, Tamer (NATL TECHNICAL UNIV ATHENS, 2006)
In this study, the analysis of a turbulent round jet discharged perpendicularly from an elevated nozzle into a crossflow is taken into account. Simulations are performed using RANS solver to analyze the effect of two-equation turbulence models on flow and reveal flow patterns, velocity and temperature fields along horizontal and vertical planes for various jet-to-crossflow momentum flux ratios. At the present study the flow is considered as three-dimensional because of its nature and turbulent with finite volume method as discretization scheme. Results observed from this numerical analysis are compared with experimental studies found in the literature.
Keywords: jet in crossflow; transverse jet; turbulent flow; computational fluid dynamics; Thermodynamics; Energy & Fuels; Engineering